ANALYSIS OF THE FEEDING OF FISH AND FISH SKIN WASTE TO THE GROWTH AND RETENTION OF PROTEIN IN DUMBO CATFISH (Clarias gariepinus) - Muh. Tsabit Mubarok; Rahmad Jumadi; Andi Rahmad Rahim (Universitas Muhammadiyah Gresik, 2020)
African catfish is the leading commodity in Indonesia, which has a speed of growth andis resistant to adverse environmental conditions. Trash fish is a small-sized fish such as fish,stingrays, rebon, turmeric fish and the like, Trash fish is also a fish that has a very loweconomic value. Trash fish has a protein content of 28.28%. Fish skin is the result of samplingfrom slaughtering animals in the form of body organs during the process of difficulty. Waste offish skins in the place of fish milling usually consists of several types of fish including grouper,payus, cob, catfish, catfish, white fish and brass fish. Fish skin waste has 26.9% protein. Thepurpose of this study was to determine the effect of trash fish feeding and fish skin wastefeeding on the growth and protein retention of African catfish (Clarias gariepinus). Knowingthe effect of feeding combined trash fish and fish skin waste on FCR of African catfish (Clariasgariepinus). This study used a completely randomized design (CRD) consisting of 4 treatmentsand 3 replications with the following measurements: (A - trash fish feed 5.3%), (B - fish skinwaste 5.77%), (C - (fish trash (50%) + fish skin waste (50%) with 5.55% administration, (K -Pellet 100% Control 5%). Main parameters include Absolute weight growth (grams), Specificgrowth rate (%), Length Absolute (cm), protein retention, survival and feed conversion ratio(FCR), while supporting parameters include temperature, pH, DO, ammonia, salinity.Researchresults were analyzed using SPSS version 17. Each data in the form of growth, survival andfeed conversion ratio (FCR) was analyzed using ANOVA (Analysis of Variance) with aconfidence level of 95%, if significance (P <0.05) continued with the Tukey test (HSD) to seedifferences between treatments Water quality data and protein retention (% ) analyzeddescriptively based on literature The results of research with pe feed of trash fish and fish skinas well as combination of trash fish (50%) + fish skin waste (50%), for the best absolute weightis the treatment K (Control) with a value of 21.03 g. The best daily growth rate is in thetreatment K (Control) with a value of 1.96% / day. The absolute length rate is in the K (Control)treatment with a value of 3.20cm. The best retention value is the treatment K (Control) with avalue of 36.32%. The lowest feed conversion ratio / FCR is control K at 1.78 g, while for thebest survival (%) is treatment B (fish skin waste) with 90% survival.